Guideline for incorporating the Delphi method in the evaluation of nursing theories - Manuela Campos Gomes Borel; Rafael Oliveira Pitta Lopes; Maira Buss Thofehrn; Maria Miriam Lima Da Nóbrega; Cristina Arreguy-Sena; Marcos Antônio Gomes Brandão (Universidade de São Paulo, 2021)
Objective: to describe a guideline for the use of the Delphi method to evaluate nursing theories, from the perspective of internal validation. Method: a methodological study, targeted at the development of a guideline for the use of the Delphi method in the evaluation of nursing theories. Results: the Delphi method, principles of collective wisdom and levels of proficiency are used in the production of a guideline for organizing, searching, selecting and coordinating the activities of theoretical evaluators in teams. It distinguishes three phases for the theoretical evaluation process: Preparatory Phase (PP); Intermediate Phase (IP) and Theory Evaluation (TE) phase, incorporating Delphi-type selection procedures; search, selection and classification of judges/evaluators for the theory; definition of criteria for carrying out rounds and maintenance or removal of units of the theory evaluated. Conclusion: the developed guideline was able to adapt the elements of the Delphi method as a favorable strategy for the internal validation of nursing theories.